2003
DOI: 10.1046/j.1365-8711.2003.06891.x
|View full text |Cite
|
Sign up to set email alerts
|

The long time-scale X-ray variability of the radio-quiet quasar PG 0804+761

Abstract: We present the results from a study of the timing properties and the energy spectrum of the radio‐quiet quasar PG 0804+761, based on monitoring RXTE/PCA observations that lasted for a year. This is a systematic study of the X‐ray variations on time‐scales of weeks/months of the most luminous radio‐quiet quasar studied so far. We detect significant variations in the 2–10 keV band of an average amplitude of ∼15 per cent. The excess variance of the light curve is smaller than that of Seyfert galaxies, entirely co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
(48 reference statements)
2
15
0
Order By: Relevance
“…PG 0804+761 (z = 0.100) PG 0804+761 was one of the brightest radio-quiet quasars observed by ASCA with a energy spectrum well represented by a simple power law model with a photon index of 2.18 +0.02 −0.03 in the 2-10 keV energy range with no significant Fe K emission detected (George et al 2000). Recently, Papadakis et al (2003) found similar results with RXTE analyzing the spectrum averaged over one year (Γ 3−15 keV = 2.10 +0.12 −0.10 and no Fe K line is statistically required). The flux variations appeared not to be associated with any spectral variations.…”
Section: Appendix A: Notes On Individual Objectsmentioning
confidence: 99%
“…PG 0804+761 (z = 0.100) PG 0804+761 was one of the brightest radio-quiet quasars observed by ASCA with a energy spectrum well represented by a simple power law model with a photon index of 2.18 +0.02 −0.03 in the 2-10 keV energy range with no significant Fe K emission detected (George et al 2000). Recently, Papadakis et al (2003) found similar results with RXTE analyzing the spectrum averaged over one year (Γ 3−15 keV = 2.10 +0.12 −0.10 and no Fe K line is statistically required). The flux variations appeared not to be associated with any spectral variations.…”
Section: Appendix A: Notes On Individual Objectsmentioning
confidence: 99%
“…We fitted both PSDs with a power-law model (PL) of the form: P( f ) = A(10 4 f ) −α + C, taking into account aliasing effects (as in Papadakis et al 2003). The constants A and C are the PL normalization (equal to the PSD value at 10 −4 Hz) and the Poisson noise level, respectively.…”
Section: The High Frequency Power Spectrummentioning
confidence: 99%
“…Markowitz & Edelson (2001) have calculated the excess variance for nine Seyfert galaxies using 300‐d‐long, RXTE Proportional Counter Array (PCA), 2–10 keV light curves with a uniform 5‐d sampling. Recently, Papadakis et al (2003) calculated the excess variance of PG 0804+761 using a 1‐yr‐long, RXTE (PCA), 2–10 keV light curve with a 3‐d sampling. The sampling and duration of the quasar light curve are similar to the respective properties of the Seyfert galaxy light curves of Markowitz & Edelson.…”
Section: The Dependence Of Long‐term Variability Amplitude On Mbhmentioning
confidence: 99%
“…Note that NGC 5506 was recently classified as NLS1 (Nagar et al 2002). All σ 2 rms estimates in column (3) are taken from Markowitz & Edelson (2001), except from PG 0804+761 which is taken from Papadakis et al (2003). The numbers in parenthesis in column (4) correspond to the references for ν hfb as follows: (1) Markowitz et al (2003), (2) Uttley et al (2002), (3) Vaughan, Fabian & Nandra (2003), (4) Vaughan et al (2003), (5) McHardy et al (2003), (6) Shih, Iwasawa & Fabian (2003), (7) Papadakis et al (2002).…”
Section: The Dependence Of Long‐term Variability Amplitude On Mbhmentioning
confidence: 99%
See 1 more Smart Citation